Brain train to combat brain drain; focus on exercise strategies that optimize neuroprotection. Issue 9 (1st September 2016) - Burley, Claire V.; Bailey, Damian M.; Marley, Christopher J.; Lucas, Samuel J. E.
New Findings: What is the topic of this review? The topic of this review is to consider innovative exercise strategies that optimize neuroprotection in order to combat cognitive decline and neurodegenerative disease in older age. What advances does it highlight? The review summarizes current understanding around exercise mode, duration, frequency and intensity, and then highlights adaptive roles of select stressors that have equal if not indeed greater capacity than exercise per se to induce health‐related adaptation in the brain. These stressors include, but are not exclusively limited to, hydrostatic and thermal stress, hypoxia, nutritional supplementation and cognitive loading, and are effective by targeting specific pathways that collectively contribute towards improved brain structure and function. The prevalence of cognitive decline and neurodegenerative diseases (e.g. stroke and dementia) is increasing. Numerous studies show that regular exercise has beneficial effects on brain health in clinical and non‐clinical populations, yet adherence to public health exercise guidelines is notoriously poor. Recently, novel exercise strategies have been investigated to allow for more individualized and prescriptive approaches that target the key mechanistic pathways that allow exercise to mediate adaptation. This work exploring alternative approaches to the traditional model of exercise training has demonstrated exciting potential for positive health‐related adaptations (especially for metabolic, muscle and cardiovascular function). However, few studies to date have focused on brain adaptations. The aim of this review is to summarize new and innovative interventions that have the potential to optimize exercise for improved brain health (i.e. brain structure and function). First, we briefly summarize current understanding of the nature whereby positive effects of exercise deliver their influence on the brain (i.e. underlying mechanisms and factors affecting its delivery). Second, we introduce the effects of exercise training on cognition and give examples of studies showing the beneficial effects of exercise in clinical populations. Finally, we explore the adaptive roles of individual stressors that may induce greater health‐related adaptations in the brain than exercise alone, including environmental stressors (hydrostatic stress, thermal stress and hypoxia), nutritional supplementation and cognitive loading. In summary, optimized interventions that target key mechanistic pathways linked to improved brain structure and function could ultimately protect against and/or ameliorate cognitive decline and neurodegenerative diseases. Abstract :